2003
DOI: 10.1128/jvi.77.22.12352-12356.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Lymphatic Mechanism of Rotavirus Extraintestinal Spread in the Neonatal Mouse

Abstract: We used the neonatal mouse model of rotavirus infection and virus strains SA11-clone 4 (SA11-Cl4) and Rhesus rotavirus (RRV) to examine the mechanism of the extraintestinal spread of viruses following oral inoculation. The spread-competent viruses, RRV and reassortant R7, demonstrated a temporal progression from the intestine, to the terminal ileum, to the mesenteric lymph nodes (MLN), and to the peripheral tissues. SA11-Cl4 was not found outside the intestine. Reassortant virus S7, which was unable to reach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 25 publications
4
57
0
2
Order By: Relevance
“…Similarly, MLN in infected infants of diabetes-resistant mice harbour infectious RRV. The cells in the MLN involved are unidentified, although mouse rotavirus replicates in dendritic cells (DC), and possibly B cells and macrophages [21,22]. The spread of rotavirus to the MLN and PLN in adult mice has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MLN in infected infants of diabetes-resistant mice harbour infectious RRV. The cells in the MLN involved are unidentified, although mouse rotavirus replicates in dendritic cells (DC), and possibly B cells and macrophages [21,22]. The spread of rotavirus to the MLN and PLN in adult mice has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation with the mouse strain EDIM and the human strain Wa caused no clinical signs of hepatobiliary injury, and consistent with the lack of injury, we found no detectable infectious virus within the liver. Previous studies have shown that the extraintestinal spread of rotavirus is strain dependent (22,23,32). In those studies, the presence of virus within the liver was used as a marker of spread (22,23).…”
Section: Vol 81 2007mentioning
confidence: 99%
“…Previous studies have shown that the extraintestinal spread of rotavirus is strain dependent (22,23,32). In those studies, the presence of virus within the liver was used as a marker of spread (22,23). The results of the current study expand on these observations showing that not only is the extraintestinal spread of rotavirus strain dependent but the specific targets of inoculation within the liver vary, which in turn, impacts the subsequent development of clinical manifestations of disease and the survival of the injected mouse.…”
Section: Vol 81 2007mentioning
confidence: 99%
“…The presence of RVA in MLNs has so far been reported in experimental animal models (Brown & Offit, 1998;Crawford et al, 2006;Dharakul et al, 1988;Fenaux et al, 2006;Kim et al, 2011;Mossel & Ramig, 2003; Park et al, Genetic analyses showed that all strains for which the genome was detected in MLNs from autopsied calves and healthy adult cattle were classified as G and/or P (possible) genotypes generally prevalent in bovines (Tables 2 and 3). Also, in most of the cattle that had RVA genomes in both MLNs and intestinal contents, the strains in intestinal contents were genetically identical to those in MLNs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been an increasing number of reports of infectious RVA and the viral antigen being detected in sera and various organs, such as mesenteric lymph nodes (MLNs), lungs and livers in humans and animals (Blutt et al, 2003;Crawford et al, 2006;Dharakul et al, 1988;Fenaux et al, 2006;Lynch et al, 2003;Mossel & Ramig, 2003). In experimental animal models, RVA has been detected not only in the gastrointestinal tract but also in extra-intestinal organs, indicating that the virus is able to spread systemically from the gastrointestinal tract (Crawford et al, 2006;Fenaux et al, 2006;Kim et al, 2011;Mossel & Ramig, 2003;Park et al, 2013Park et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%